EXTRACTION OF TARTARIC ACID FROM TAMARIND PULP AND ANALYSIS OF THE ACID COMPOSITION IN LEAVES - Roopa, Gullipalli Santhosh; Kasiviswanatham, V. (International Journal of Students’ Research in Technology & Management, 2015)
Tamarind a naturally obtained, long lived, evergreen and less expensive raw material. It comprises organic acids like high content of tartaric acid 12-18%, malic acid, citric acid and byproducts like pectin, potassium Bitartrate. The purpose of this research was to extract the tartaric acid from tamarind pulp by hot and cold extraction followed by cooling and by addition of less expensive chemicals. The obtained solid form of acid detected with NMR Spectra and its concentration analyzed with UV spectrophotometer using metavanadate. Where as the composition of acid in powdered form of leaves explored with two methods. By organic extraction using suitable solvent, the composition of acid in leaves is extracted using own making equipment percolator with small lab scale apparatus and waste material like plastic drink bottle and another method is soxhlet apparatus. The extracts obtained from process are added with another suitable solvent and were analyzed by Thin Liquid Chromatography. As a whole the process becomes economically more competitive than other process and to utilize the product in both traditional and agricultural applications.